(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The aim of the research work is consists in identifying different and similar aspects of semantically-functionally formed word-sentences and canonical model speech derivatives on the basis of system-structural, linguodidactic and comparative analysis of canonical model sentences in French and Uzbek languages.